2005
DOI: 10.1002/anie.200462543
|View full text |Cite
|
Sign up to set email alerts
|

From Racemic Primary Aminoalkyl(phosphanyl)ferrocene Complexes to a Lithium–Phosphorus closo Cluster

Abstract: Li12P6: The first two primary aminoalkyl(phosphanyl)ferrocene complexes 2‐(N,N‐Dimethylaminomethyl)phosphanylferrocene (1) and N,N‐dimethyl‐1‐(2‐phosphanylferrocenyl)ethylamine (2) are prepared. Compound 1 readily undergoes twofold deprotonation with nBuLi to form the first lithium–phosphorus cluster (see picture) which has the structure and electronic properties of a closo cluster according to Wade's rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Thus, compounds 5 and 6 were obtained by reaction of crude 3 or 4 with LiAlH 4 (Scheme 1) in shorter time and much better yield than reported by us previously. 14 Phosphane 6 is a crystalline solid whose structure is depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, compounds 5 and 6 were obtained by reaction of crude 3 or 4 with LiAlH 4 (Scheme 1) in shorter time and much better yield than reported by us previously. 14 Phosphane 6 is a crystalline solid whose structure is depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…We have already shown that 5 can be lithiated twice and that the resulting dilithium phosphanediide forms a hexameric aggregate with a central Li 12 P 6 unit which can be described as a closo cluster. 14 To extend this chemistry, a similar reaction was performed with (R,S)-9 as starting material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BH 3 (THF) (1 M in THF) was purchased and purified by bulb‐to‐bulb vacuum distillation before use. [Fe(C 5 H 5 ){C 5 H 3 (CH 2 NMe 2 )PH 2 }],17b [{Rh(μ‐Cl)(cod)} 2 ],38 [FcCH 2 PH 2 ],39 [FcPH 2 ],40 and [FcCH 2 PH 2 (BH 3 )]20 were synthesized according to literature procedures. NMR spectra were recorded with a Bruker AVANCE DRX 400 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Only some larger derivatives, mostly containing lithium,a re known in the literature. [38,40,[46][47][48][49][50][51][52][53][54][55][56][57] In contrast to compound 5,t he coordination number of the phosphorus atom in 6 increases to five. The potassium atoms coordinated by two phosphorus atoms (K1 and K1')h aveac oordination number of six (2 P, 2 O, 2 CH 3 agostici nteraction with the methyl groups of the tBu substituents), whereas the potassium atoms solely coordinated by one phosphorusa tom show one agostici nteraction to am ethyl group (K2, K2',K 3, and K3').…”
mentioning
confidence: 99%